Klasifikasi Penderita Penyakit Gagal Jantung Menggunakan Metode Support Vector Machine (SVM) - Dwi Febriansyah (2023)
One of the cardiovascular diseases that is very dangerous to health and affects many people around the world is heart failure. Decisions about appropriate medical treatment can be made by detecting and classifying heart failure sufferers early. This research aims to use the Support Vector Machine (SVM) method to determine who has heart failure. The SVM method creates a hyperplane separating the two data classes with maximum margins. It is one of the most common and effective machine-learning methods for data classification. SVM can predict heart failure by studying patterns from relevant medical data, this is used in the classification of heart failure. Keywords: heart failure, support vector machine, classification, machine learning